DESAIN MATRIKS NANOPARTIKEL KITOSAN UNTUK PERCEPATAN PENYEMBUHAN LUKA - Syafitri, Erga
Wound is a destruction of the anatomical structure and function of the skin. The loss of the extracellular matrix of cells, microbial infection and excess fluid from the wound exudate can slow the healing process. This research has developed a chitosan-based wound dressing formula that strong and elastic, has a good water absorption capacity, not easily penetrated by microbes, generate pores in the range of 100-300 ?m, and can be used for 6 days. Matrix wound dressing was made of high molecular weight (MW) chitosan, plasticizer, and low MW chitosan as a porogen. Chitosan nanoparticles were made using ionic gelation method with the addition of sodium tripolyphosphate (STPP) as a cross-linker. Then the nanoparticles were dispersed in a matrix of chitosan consisting of MW chitosan and the plasticizer until homogeneous and then dried using an oven. The optimization type of plasticizer, the combination of chitosan, and drying time matrix were done. Various matrix fomulas were characterized and evaluated including physical properties, mechanical properties, water absorption capacity, morphology and porosity, degradation rate, and microbial penetration in vitro. Among these formula, formula M4 showed the optimum characteristics with composition of low MW chitosan:high MW chitosan was 2.5:1.5 (w/w), composition of chitosan:propylene glycol was 1:2.5 (w/w), and low MW was added in the form of nanoparticle with composition low MW chitosan:STPP was 2:0.6 (w/v). The mechanical strength of this formula was 142.73 ± 15 g, the elasticity was 43.03 ± 5%, maximum water absorption capacity was 146.9 ± 1.5%, porosity was 79.32 ± 3.0%, pore size in the range of 47.92 – 193.7 µm, and no evidence of microbial penetration. This matrix can be applied for six days.